The Effect of Corporate Governance and Intellectual Capital on Capital Structure and Financial Distress - Candradewi, Made Reina; Rahyuda, Henny; Pereira, José Agostinho da Costa Belo (Universitas Mercu Buana, 2025)
Objectives : This study aims to conduct an in-depth analysis of the influence of corporate governance and intellectual capital on capital structure and financial distress in manufacturing companies on the Indonesia Stock Exchange (IDX) from 2020 to 2022. This study is expected to help companies overcome financial distress problems and determine the optimal capital structure by considering the implementation of good corporate governance and intellectual capital management. This study is also expected to enrich the scientific knowledge of financial management regarding the relationship between corporate governance, intellectual capital, capital structure, and financial distress.Methodology : This research is a study with a quantitative approach. The sampling technique in this study is the purposive sampling method, with the criteria for determining the sample, namely manufacturing companies that are always listed on the IDX from 2020 to 2022. Thus, the final sample in this study is estimated to be 187 manufacturing companies.Finding : The regression analysis and mediation test results show that the Corporate Governance variable does not significantly affect Capital Structure. The Intellectual Capital variable has a significant negative effect on Capital Structure. In addition, the corporate governance variable was found to affect financial distress significantly and negatively. However, Intellectual Capital and Capital Structure were found to have no significant effect on Financial Distress. The Capital Structure variable could not mediate the relationship between Corporate Governance and Intellectual Capital in Financial Distress.